WORKPLACE BULLYING AGAINST PUBLIC EMPLOYEES - Pellegrini, Priscila Gasperin (2017)
This qualitative study was developed with the purpose of characterizing the experience of working women from public organizations in relation to workplace bullying. Four women, public employees, participated in the research. The data collection was performed through individual semi-structured interviews and the data obtained were analyzed and categorized according to the thematic categorical content analysis. The results showed cases of bullying that were characterized mainly as vertical downward, from the superior to the subordinate and the abuse of power as an aggravating factor in cases of bullying with women in public organizations. It’s important to consider that women were identified as perpetrators of aggression, which highlights the need to analyze gender aspects of the victim and aggressor, as well as organizational culture.